HIV-1 is rarely detected in blood and colon myeloid cells during viral-suppressive antiretroviral therapy. (1st July 2019) - Cattin, Amélie; Wiche Salinas, Tomas Raul; Gosselin, Annie; Planas, Delphine; Shacklett, Barbara; Cohen, Eric A.; Ghali, Maged P.; Routy, Jean-Pierre; Ancuta, Petronela
Abstract : Objective: The aim of this study was to explore the contribution of blood and colon myeloid cells to HIV persistence during antiretroviral therapy (ART). Design: Leukapheresis was collected from HIV-infected individuals with undetectable plasma viral load during ART (HIV + ART; n = 15) and viremics untreated (HIV+; n = 6). Rectal sigmoid biopsies were collected from n = 8 HIV+ART. Methods: Myeloid cells (total monocytes (Mo), CD16 + /CD16 − Mo, CD1c + dendritic cells) and CD4 + T cells were isolated by magnetic-activated cell sorting (MACS) and/or fluorescence-activated cell sorting (FACS) from peripheral blood. Matched myeloid and CCR6 + CD4 + T cells were isolated from blood and rectal biopsies by FACS. Levels of early (RU5 primers), late (Gag primers) and/or integrated HIV-DNA (Alu/HIV primers) were quantified by nested real-time PCR. Replication-competent HIV was amplified by co-culturing cells from HIV-positive individuals with CD3/CD28-activated CD4 + T cells from uninfected donors. Results: Early/late but not integrated HIV reverse transcripts were detected in blood myeloid subsets of four out of 10 HIV+ART; in contrast, integrated HIV-DNA was exclusively detected in CD4 + T cells. In rectal biopsies, late HIV reverse transcripts were detected in myeloid cells and CCR6 + CD4 + T cells from one out of eight and seven out of eight HIV+ART individuals, respectively. Replication-competent HIV was outgrown from CD4 + T cells but not from myeloid of untreated/ART-treated HIV-positive individuals. Conclusion: In contrast to CD4 + T cells, blood and colon myeloid cells carry detectable HIV only in a small fraction of HIV+ART individuals. This is consistent with the documented resistance of Mo to HIV infection and the rapid turnover of Mo-derived macrophages in the colon. Future assessment of multiple lymphoid and nonlymphoid tissues is required to include/exclude myeloid cells as relevant HIV reservoirs during ART. Abstract : Supplemental Digital Content is available in the text